The Association between Maternal Knowledge, Family Support, and Exclusive Breastfeeding in Siborong Borong Community Health Center, North Tapanuli, North Sumatera - Sipahutar, Selferida; Lubis, Namora Lumongga; Siregar, Fazidah Agusliana (Journal of Maternal and Child Health, 2019)
Background: Exclusive breastfeeding means that the infant receives only breast milk. No other liquids or solids are given